The remarkable three-dimensional network structure of bacterial cellulose for tissue engineering applications - Nadia Halib; Ishak Ahmad; Mario Grassi; Gabriele Grassi (Elsevier B.V., 2024)
Indexed by WOS/Scopus/ERA